Parent's perception of their children's health, quality of life and burden of diabetes: testing reliability and validity of 'Check your Health' by proxy. Issue 3 (21st July 2016) - Brorsson, Anna Lena; Lindholm Olinder, Anna; Wikblad, Karin; Viklund, Gunnel
Abstract : Aim: To test the validity and reliability of the 'Check your Health by proxy' instrument in parents to children with diabetes aged 8–17 years. Methods: One hundred and ninety‐one caregivers and their children, aged 8–17 years, were included. All completed the 'Check your Health' questionnaire measuring quality of life and burden of diabetes, DISABKIDS self‐ or proxy version, and 45 completed the same questionnaires 2 weeks later. Results: Test–retest reliability on the 'Check your Health' questionnaire by proxy was moderate to strong ( r = 0.48–0.74), p < 0.002). Convergent validity was weak to moderate ( r = 0.15–0.49, p < 0.05). The instrument showed acceptable discriminant validity. Parents reported lower scores than the children on emotional health and social relations and higher scores on physical and emotional burden and higher burden on quality of life. Poorer social relationships and quality of life were associated with higher reported disease severity. The diabetes burden domain of the questionnaire correlated to perceived severity of diabetes and to perceived health. Discriminant validity showed that poorer social relationships and quality of life were associated with higher severity of the disease. The diabetes burden domain of 'Check your Health' by proxy showed discriminant validity on perceived severity of diabetes. Conclusions: The instrument 'Check your Health' by proxy showed acceptable psychometric characteristics in parents to young people (8–17 years of age) with diabetes. We also concluded that parents reported that their children had lower health and higher burden of diabetes than the children did, and it correlated to reported disease severity.